INHERITED VARIATIONS IN DRUGS EFFECT INDEPENDENT IN PHARMACOKINETIC: POLYMORPHISM IN PHASE II BIOTRANSFORMATION ENZYMES - Muhammad Ricky Ramadhian (JUKE Unila, 2014)
Phase II enzymes play an important role in the biotransformation of endogenous compounds and xenobiotics to more easily excretable forms as well as in the metabolic inactivation of pharmacologically active substances. The purpose of phase II biotransformation is to perform conjugating reactions. These include glucuronidation, sulfation, methylation, acetylation, glutathione, and amino acid conjugation. In general, the respective conjugates are more hydrophilic than the parent compounds. Polymorphism in Phase II drug metabolism enzymes may have role in diseases, cancer, and others. This review discuss brief about polymorphism in Phase II drug metabolism enzyme. [JuKe Unila 2014; 4(8):254-268]